The power of emotion regulation: how managing sadness influences depression and anxiety? - Sumaia Mohammed Zaid; Fonny Dameaty Hutagalung; Harris Shah Bin Abd Hamid; Sahar Mohammed Taresh (BMC Psychology)
Abstract Background Emotions are a fundamental part of life and play a critical role in shaping individuals’ experiences Effectively regulating emotions in socially appropriate ways is essential for navigating life successfully. This study investigated the impact of seven sadness regulation strategies on depression and anxiety and examined the mediating role of ER in the relationship between sadness regulation and depression and anxiety. Method A cross-sectional design was employed with 350 participants (144 men, 206 women) aged 18 to 35. Results Regression analyses showed that sadness regulation strategies significantly predict both depression and anxiety. For depression, the model explained 18.6% of the variance (F (7,342) = 11.140, p < 0.001), with cognitive reappraisal, religious coping, and seeking support negatively associated, while rumination was positively associated. For anxiety, the model explained 19% of the variance (F(7,342) = 11.484, p < 0.001), with rumination and substance use linked to lower anxiety levels, while other strategies showed no significant associations. Mediation analyses highlighted emotion regulation critical role, with sadness regulation influencing depression indirectly through ER (β = -0.024, 95% CI [-0.040, -0.009]) and accounting for 3.6% of the variance. Sadness regulation also had a direct (β = -0.037, p < 0.001) and indirect effect on anxiety through emotion regulation, explaining 6.1% of the variance. Conclusion These findings underscore the importance of adaptive sadness and emotion regulation strategies in mitigating depression and anxiety, offering valuable insights for therapeutic interventions.